Syria's uneasy bedfellows: Perpetuation of conflict serves radicals, prospect for compromise increases moderation - Khaled Yacoub Oweis; Heiko Wimmen (Stiftung Wissenschaft und Politik (SWP), 2016)
The siege of Aleppo and the mounting losses of opposition districts throws a central dilemma for the Syrian rebels into sharp relief: if they hope to hold out against the Assad regime and its Russian and Iranian backers, they cannot forego the support of extremist Jihadi groups. Yet it is the prominent role of these same extremists that provides the justification for the Russian intervention and the excuse for Western powers to withhold support for the rebellion. Events in recent months have shown that the prospect of starting a political process furthers the position of moderate and non-Jihadi Islamists and helps isolate the extremists. Germany and its European allies should insist on committing Russia to the diplomatic process and encourage supporters of the Syrian opposition to work towards consolidating actors compatible with a potential transition process. (SWP Comments)
Keywords: 320